Pengaruh Social Media Marketing, Word Of Mouth, Dan Citra Destinasi Terhadap Minat Berkunjung Pada Taman Nasional Bromo Tengger Semeru (Studi Kasus Pada Generasi Z di Kota Malang) - Antika, Meggy Tri; Susyanti, Jeni; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Currently, Indonesia has many tourist destinations that can be used as assets for the government to develop regional tourism by relying on the internet. One such tour is the Bromo Tengger Semeru National Park. The aim of this type of explanatory research and quantitative approach is to find out and analyze social media marketing, word of mouth, and destination image on visiting intentions, either simultaneously or partially. The sampling technique used is a non-probability sampling technique, namely snowball sampling which is a technique for determining the initial sample size is small, then enlarges. Determining the number of samples using the Malhotra formula which then found a number of 95 respondents. This research method uses multiple linear regression analysis with the SPSS analysis tool. Based on the results of this study, social media marketing, word of mouth, and destination image partially have an influence on visiting intentions. Keywords: Social Media Marketing, Word Of Mouth, Destination Image And Interest In Visiting